Computed tomography-derived fractional flow reserve (FFRCT) has no additional clinical impact over the anatomical Coronary Artery Disease - Reporting and Data System (CAD-RADS) in real-world elective healthcare of coronary artery disease. Issue 12 (December 2022) - Hamilton, M.C.K.; Charters, P.F.P.; Lyen, S.; Harries, I.B.; Armstrong, L.; Richards, G.H.C.; Strange, J.W.; Johnson, T.; Manghat, N.E.
Abstract : AIM: To evaluate the impact of computed tomography-derived fractional flow reserve (FFRCT ) compared to the anatomical Coronary Artery Disease - Reporting and Data System (CAD-RADS) in the elective assessment of coronary artery disease in real-world cardiology practise. MATERIALS AND METHODS: A retrospective review was undertaken of 1, 239 coronary CT examinations from August 2018 to December 2019 with a minimum follow-up period of 1 year. Coronary disease was classified according to the CAD-RADS system. A non-occlusive ≥30% maximum diameter stenosis was considered eligible for FFRCT . Lesion-specific FFRCT and FFR were considered positive if ≤ 0.80. The patients were followed up using the hospital radiology information system and the electronic patient record. A positive outcome was defined by a subsequent invasive angiogram (ICA) showing disease requiring revascularisation or FFR ≤0.80 or a positive stress test or medical therapy for angina in CAD-RADS 4. RESULTS: Of the 1, 145 analysable studies (mean follow up 618 ± 153 days) the incidence of a positive result was 7% with a 5.4% elective revascularisation rate. Two hundred and forty-five patients (CAD-RADS 2–4) had FFRCT . FFRCT reduced the accuracy of the CAD-RADS grade from 91% to 78.4% ( p< 0.001). In CAD-RADS 2, the accuracy is reduced from 99% to 90.7% ( p= 0.005), and in CAD-RADS 3 from 93.9% to 67.7% ( p< 0.001). In CAD-RADS 4, FFRCT increases accuracy from 69.4% to 75.5% ( p= 0.025), but 89.8% of FFRCT are positive and specificity is low (26.7%). CONCLUSION: In the present "real-world" practise, FFRCT does not improve standard radiological assessment of coronary disease graded by the CAD-RADS alone. Highlights: In CAD-RADS 2, FFRct reduces CTCA accuracy for predicting a positive outcome. In CAD-RADS 3, FFRct reduces CTCA accuracy for predicting a positive outcome. In CAD-RADS 4, FFRct marginally improves CTCA accuracy for a positive outcome. In CAD-RADS 4, FFRct has poor specificity. In CAD-RADS 2–4, FFRct overall reduces the accuracy of CTCA.